2021
DOI: 10.3390/pathogens10081029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Confirmation of Massive Taenia pisiformis Cysticercosis in One Rabbit in Poland

Abstract: The aim of this study was to provide molecular characterization, together with phylogenetic analysis, of Taenia pisiformis cysts isolated from rabbit. On the basis of morphological features and molecular analysis, the cysticerci were identified as T.pisiformis metacestodes. PCR was performed with three different protocols to obtain partial sequences of 12S ribosomal RNA (12S rRNA), NADH dehydrogenase subunit 1 (nad1), and cytochrome oxidase subunit 1 (cox1) of Taenia spp. The products from the PCRs were sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…The second PCR employed in the present study amplified a partial sequence of cytochrome c oxidase subunit 1 ( cox1 fragment gene) using a protocol designed by Bowles et al [ 44 ] and modified by Casulli et al [ 45 ], which has been described previously [ 43 ] and is reported in Table 1 . The PCR amplified a fragment to about 446 bp using primers CO1F and CO1R ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…The second PCR employed in the present study amplified a partial sequence of cytochrome c oxidase subunit 1 ( cox1 fragment gene) using a protocol designed by Bowles et al [ 44 ] and modified by Casulli et al [ 45 ], which has been described previously [ 43 ] and is reported in Table 1 . The PCR amplified a fragment to about 446 bp using primers CO1F and CO1R ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Подібні дослідження були проведені у Польщі. Молекулярно підтверджено метацестоду T. Pisiformis у кроликів (Samorek-Pieróg et al, 2021). Лікування личинкової стадії C. pisiformis цестоди T. pisiformis не розроблене.…”
Section: поширення діагностика та лікування гельмінтозних хвороб кролівunclassified
“…Cysticercus pisiformis is a widely prevalent larval form of tapeworm that primarily parasitizes the liver, omentum, and mesenteries of lagomorphs and rodents, leading to the development of cysticercosis pisiformis ( 1 , 2 ). Among these hosts, rabbits are the most frequently affected and suffer significant consequences from cysticercosis pisiformis.…”
Section: Introductionmentioning
confidence: 99%